PERADABAN ISLAM DI NUSANTARA PRA KEMERDEKAAN DAN PERKEMBANGAN PENDIDIKANNYA - Salma Salsabila; Zahro Julia Agustin; Dianatus Sa’baniyah; Anang Sholikhuddin (CV. BAROKAH PUBLISHER, 2026)
Islamic civilization in the Indonesian archipelago during the pre-independence period significantly contributed to the formation of the social, political, cultural, and educational structures of Indonesian society. The process of Islamization, which took place through trade, marriage, the preaching of Islamic scholars, and the development of Islamic kingdoms, gave birth to centers of civilization such as Aceh, Demak, Banten, and Ternate. This research uses a literature study method by examining scientific articles indexed by Google Scholar on the history of Islam and Islamic education in the Indonesian archipelago. The results show that the development of Islamic education before independence was realized through traditional institutions such as Islamic boarding schools (pesantren), surau (surau), dayah (dayah), and langgar (prayer houses), which functioned as centers for the transmission of Islamic knowledge, moral development, and the development of clerics and community leaders. Furthermore, Islamic educational institutions served as a means of cultural resistance against colonialism and a medium for the formation of the community's identity. In the early 20th century, Islamic education underwent renewal through the madrasah system, which began to integrate religious and general knowledge. Thus, Islamic civilization in the pre-independence Indonesian archipelago not only left a religious and cultural legacy but also laid an important foundation for the development of national education in Indonesia